Analysis of the Anticancer Potential of Green Tea’s EGCG Component to Inhibit Immortal Cells - Stillwell, Allayah; Treml, Jack; Logan, Randall (Midwestern Journal of Undergraduate Sciences, 2022)
Green tea has a high abundance of catechins and other antioxidants found organically within its composition. In recent studies, a polyphenolic catechin, referred to as EGCG, has shown the potential to promote advancements in the development of non-harmful cancer treatments. Several experimental questions were explored regarding EGCG, including the concentration of EGCG present in commercial green teas, its anticancer potency, and EGCG’s potential contributions to cell cycle arrest. Briefly, a green tea extract was prepared utilizing ground green tea leaves and a polar extraction method. The fluorescent properties of EGCG were exploited to quantitate its concentration in green tea preparations in comparison to a purified EGCG standard. The anticancer potency of EGCG was then assessed by exposing HeLa (cancer cells) and MRC-5 (primary) cells to green tea extract- containing the EGCG component- for 24 hrs. The cells were evaluated for viability, suggesting that higher concentrations of extract exerted specificity toward cancer cells over the control model. Lastly, HCT-116 cancer cells were evaluated for cell cycle arrest following drug treatment. Results indicated that green tea extract imposed a cytotoxic effect selective to cancer cells while avoiding cytotoxicity to a primary cell model. In addition, treated cancer cells experienced an increase in the cell population at the G1 phase, indicating a halt in the cell cycle. This hypothesis was supported by an observed decrease in cell population in the S phase. These results show the potential for green tea extracts containing EGCG to be potential components in cancer therapeutics and/or preventatives.